Development Of Real-Time Lora-Based Air Pollution Monitoring System - Mohd Shaari Azyze, Nur Latif Azyze; Md Isa, Ida Syafiza; Kamaruzaman, Nur Syahirah (Asian Research Publishing Network (ARPN), 2021)
Air pollution can cause long-term health effects on humans, such as heart disease, lung cancers, and respiratory disease. There are many forms of contamination induced by smoke or gas emissions due to fossil fuel burning from transportation. Furthermore, manufacturing operations also negatively impact the air quality, where the production of plastics, electronics, and rubber, has contributed to a rise in organic carbon, inorganic carbon, and dust contaminations. Therefore, in this work, a real-time air pollution monitoring system has been developed to monitor air quality considering three types of gas sensors which are MQ2, MQ7 and MQ135. Also, LoRa communication technology is used as the communication modules between the sensor node located at the site and the gateway. The system is also equipped with an additional notification system to send the monitored air concentration data to the control room via the Telegram application. For monitoring purposes, the monitored data from the sensors will be updated every 5 minutes in the server using the Node-Red platform. The performance of the developed system has been evaluated considering six different distances between the sensor node and gateway, and the results show that the system has high reliability. The results also indicate that the average received signal strength indicator (RRSI) value of the LoRa module between the sensors and gateway reduced with the increasing distance between the sensor node and gateway. However, this does not affect the performance of the developed system.